Manajemen Kurikulum Pesantren Modern dalam Meningkatan Mutu Lulusan - Imroatus Sholihah; Muhibbin Syah; Badrudin Badrudin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2022)
Curriculum management is the process of utilizing all management activities, starting from planning, implementing and evaluating in order to maximize the achievement of educational curriculum objectives implemented in educational institutions. The facts on the ground show that TMI Al-Amien Prenduan has implemented curriculum management activities, namely the planning, implementation and evaluation processes. The purpose of this study was to identify the planning of the modern Islamic boarding school curriculum at the TMI Al-Amien Prenduan Modern Islamic Boarding School, the implementation of the modern Islamic boarding school curriculum at the TMI Al-Amien Prenduan Modern Islamic Boarding School and the evaluation of the modern Islamic boarding school curriculum at the TMI Al-Amien Prenduan Modern Islamic Boarding School. This study uses a qualitative approach through interviews, observation and documentation. As a source of triangulation, in-depth interviews were conducted with other informants, namely the deputy head of the curriculum, curriculum staff, general secretary, infrastructure staff and teachers. The results showed that the management of the pesantren curriculum at TMI Al-Amien Prenduan was effective in a systematic way from planning, implementing and evaluating realistically and influencing success in the learning process to improve the quality of graduates.